2018
DOI: 10.1007/s12975-018-0623-1
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Leukocyte Counts Drive the Differential Expression of Transcriptional Stroke Biomarkers in Whole Blood

Abstract: Our group recently identified a panel of ten genes whose RNA expression levels in whole blood have utility for detection of stroke. The purpose of this study was to determine the mechanisms by which these genes become differentially expressed during stroke pathology. First, we assessed the transcriptional distribution of the ten genes across the peripheral immune system by measuring their expression levels on isolated neutrophils, monocytes, B-lymphocytes, CD-4+ T-lymphocytes, CD-8+ T-lymphocytes, and NK-cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Several prior studies have performed genome-wide transcriptomic profiling of peripheral whole blood with the goal of identifying clinically-useful stroke biomarkers [2, 3, 4, 5, 6]. Recent work by our group suggests that similar to other conditions [7], several of the gene expression changes observed between stroke patients and controls in these investigations were likely artifacts of underlying changes in leukocyte counts, and not true changes in transcription at the cellular level [8,9]. Transcriptomic deconvolution is a process which leverages such phenomena to informatically infer the cellular composition of complex biological samples based on aggregate gene expression through the analysis of cell-specific transcripts [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies have performed genome-wide transcriptomic profiling of peripheral whole blood with the goal of identifying clinically-useful stroke biomarkers [2, 3, 4, 5, 6]. Recent work by our group suggests that similar to other conditions [7], several of the gene expression changes observed between stroke patients and controls in these investigations were likely artifacts of underlying changes in leukocyte counts, and not true changes in transcription at the cellular level [8,9]. Transcriptomic deconvolution is a process which leverages such phenomena to informatically infer the cellular composition of complex biological samples based on aggregate gene expression through the analysis of cell-specific transcripts [10].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the 10 genes used as stroke predictors in [7, 8] are differentially expressed between myeloid and lymphoid leukocytes, so that the change in relative cell count explains most of the observed variation [40]. Among these genes is ID3 , which is also a predictor gene in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…It has become increasingly evident that stroke triggers a general activation of the innate arm of the peripheral immune system, and a general suppression of the adaptive arm of the peripheral immune system [ 11 , 12 ]. Accordingly, numerous prior studies of both ischemic and hemorrhagic pathology have reported that stroke induces an increase in circulating numbers of neutrophils and monocytes, and a simultaneous decrease in the number of circulating lymphocytes [ 13 , 28 31 , 35 37 ]. Our results are highly consistent with these prior reports, as some of the most statistically significant differences we observed between stroke patients and controls were in these three cell populations.…”
Section: Discussionmentioning
confidence: 99%